Correlações entre passes, finalizações, consumo de oxigênio máximo, fatores motivacionais e ansiedade em jogadores de uma equipe sub-19 no campeonato estadual de futsal do Maranhão em 2019 - FERREIRA, Sérgio Costa (2020)
ABSTRACT The aim was to correlate the technical skills of the pass and the finishes with maximum oxygen consumption, motivation and anxiety in under-19 futsal players. Materials and Methods: The sample consisted of 12 under-19 futsal players; with mean age, in years, of 17.90 ±0.83, of body mass in kg of 69.89 ±12.73, of height in meters of 1.76 ±0.05, of the percentage of fat (%G) 11.73 ±8.25; the percentage of lean mass of 60.98 ±7.68, with practice time of more than 3 years, training time of 1 to 2 hours per week and 91.66% with high school education; for skills, passes, finishes, attack-defense and defense-attack transitions were quantified, to estimate maximum oxygen consumption, Yo-Yo IR-1 was applied; and the PMQ Motivation questionnaires and CSAI-2 for Anxiety. Results: the data showed an average of 286.66 passes / game, an average of 245.66 right passes / game and an average of 41 wrong passes / game; the majority of passes occurred in the defensive sector, as well as the wrong passes; and 9 submissions generated goals (8.10%); predominance of defense-attack transitions, in the 3 games of 274 actions, 98 (1st game), 107 (2nd game) and 69 (3rd game) and 136 attackdefense actions in all; the mean value of the maximum VO2 was 47 ± 4.12 ml / kg / min; Motivation was related to competitive factors such as Competition, Technical Competence; Cognitive Anxiety was Low, Average Somatic Anxiety and High SelfConfidence; in terms of analytical statistics, there were differences (p=0.0036) in the first game, (p=0.0052) in the second game, (p=0.0007) in the third game and a strong and positive correlation between right pass and wrong finish in games; Between right and wrong pass there were differences in the games and it correlated strongly and positively with the maximum VO2; Between right pass and somatic anxiety, there was a strong and positive correlation, and differences (p=0.0229) only in the 2nd game; Between wrong pass and Cognitive Anxiety there were differences (p=0.0531) and the correlation was moderate and negative in the 2nd game; Between wrong finishing and maximum VO2 there was a moderate and positive correlation in the 1st game. In the 3rd game, there were differences (p=0.0197) and a strong and positive correlation; Between correct completion and maximum VO2, there were differences (p=0.0713) in the 1st game and the correlation was positive and moderate; Between sure finishing and Selfconfidence, there was significance and a strong negative correlation in the 1st game; In the 2nd game, there was significance (p=0.0433) and moderate positive correlation. Between the wrong ending and Cognitive Anxiety there was significance (p=0.0570) and a negative and moderate correlation in the 2nd game; In that same game, there was significance (p=0.0181) and a positive and strong correlation between wrong completion and Somatic Anxiety; There was no correlation and differences between the right pass and motivational factors; The wrong pass and motivation showed no differences or correlation in the games. Conclusion: Then, there was a correlation between right pass and wrong finish, and correlation between pass and Anxiety / Self-confidence, and the pass / finalization correlated with VO2. Moreover the pass and finish did not correlate with motivation. Thus, and due to the data, although there are correlations between the variables, they are not yet sufficient, in a complete way, to affirm the correlation